The Critique of Margin Call’s Film with Ethical Decision-Making in Critical Situations - Mohammad Reza Hamidizadeh; Fatemeh Ordoo (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to criticize Margin Call’s film content and evaluate screenplay sequences, actors’ dialogues, organizational behavior, and other management topics based on the right and ethical decision making of managers in critical situations. The descriptive-analytic research method is a kind of content that has been criticized for the reaction of people in critical situations to organizational problems, and in this regard, the strengths and weaknesses of the film have been reviewed and criticized. One of the most important strengths is a strong screenplay, in which almost all management issues are included in times of crisis. The director has displayed all the dialogues in a very simple and fluid manner based on economic terms. It is also possible to point out the crisis formation in the organization and the reversal process of directors’ decisions away from addiction. In the end, after displaying individual conflicts among individuals, holding numerous meetings, reviewing all the opinions, decisions, and competitive strategies as well as the organization’s survival, it has been shown people’s reaction in times of crisis, and Decision making as well. In addition, the lack of innovation in organizational decisions when overcoming the difficulties and all decisions made by executives showed the primacy of organizational and individual interests over the interests of other stakeholders, which were its weaknesses. Ultimately, this film is recommended for Business Professional Ethics Training to Students in this field.